Comparison of the Effectiveness 3% Tranexamic Acid Cream Versus 4% Hydroquinone Cream for Treatment of Epidermal Type Melasma - Hartika Ketty Marpaung; Theresia L. Toruan; Yuli Kurniawati; Theodorus (HM Publisher, 2021)
Background: Melasma is an acquired hypermelanosis in areas that are exposed to sun. especially in face. Severity of melasma is measured using modified Melasma Area Severity Index (mMASI) and Melanin Index (MI). Hydroquinone (HQ) is an effective drug and also a gold standard in terms of melasma treatment. However. thedrawback of hydroquinone is the treatment duration which is quite long. the occurence of side effects. and also recurrence potential. Several recent studies shows that one of the anti-pigmentation agent options. the tranexamic acid (TA). is able to prevent melanocyte activation. The results of various studies found that the use of TA showed a significant improvement in MASI scores. Objective: To compare the effectivity of 3% TA cream with 4% HQ cream as an alternative therapy in epidermal type melasma treatment. Methods: A double-blind. matched. randomized clinical trial was conducted during July 2019 until August 2019 at Dr. Mohammad Hoesin General Hospital Palembang. Subjects were divided into two groups. The first group. consists of 30 participants. get 3% TA cream; and the second group. consists of 30 participants. get 4% HQ cream. Subjects who fulfilled the inclusion criteria was included through a simple randomization. Study subjects wer given random cream pot (with label A or B on it) according to the result of simple randomization. Finally. every subjects’ melasma severity was measured using mMASI and mexameter ® . Results: There were differences in terms of baseline. 4 th weeks and 8 th weeks after treatment mMASI scores in 3% TA and 4% HQ group. At 8 th week. the mMASI score the 3% TA group was lower than 4% HQ group. There was no differences in baseline. 4 th weeks and 8 th after treatment MI between the two groups. Melanin index for 3% TA group was lower than 4% HQ group. Conclusion: Three-percent TA cream and 4% HQ cream is effective in decreasing mMASI score and MI in epidermal type melasma. There were differences in terms of the mMASI score during the 8th week after treatment between 3% TA and 4% HQ group.